(untitled) (Latakia University Journal -Medical Sciences Series, 2023)
This study aims to compare between bulk-fill composite resin and conventional nano-hybird composite resin in terms of surface roughness. Material and methods: forty stainless steel cylinders were prepared and were divided into two groups , each containing 20 cylinders . Group 1 : GRANDIO ,conventional nano-hybird composite resin . Group 2 : Xtrafill : bulk-fill composite resin. Each cylinder was filled with slightly over-molded composite resin , the edges were finished and then the surface was polished with DENJOY system in three stages .Then the samples were examined using a surface roughness tester . Statistical tests were conducted using SPSS program. Results: the T Student test showed that there is no statistically significant difference between the two research samples in terms of the studied variable , which is the surface roughness , as P=0.384 (P>0.05). Conclusion : within the limits of this study , we find that there is no significant difference in surface roughness between the bulk-fill composite resin and the conventional nano-hybird composite resin.